The utility of elastography during EBUS‐TBNA in a population with a high prevalence of anthracosis. (19th February 2020) - Abedini, Atefeh; Razavi, Fatemeh; Farahani, Mehrdad; Hashemi, Marzieh; Emami, Habib; Mohammadi, Forouzan; Kiani, Arda
Abstract: Background: Ultrasound elastography, is a pioneer sonographic modality that is conducted during endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) in order to increase the accuracy of sampling location. The current study aims to evaluate the usefulness of elastography during EBUS‐TBNA in a population with a high prevalence of anthracosis. Methods: This prospective single‐blinded study was performed on 69 lymph nodes (LNs) of patients with mediastinal lymphadenopathy undergoing EBUS‐TBNA and EBUS‐elastography from October 2017 to July 2018. The stiffness level of the tissue was translated into a color to demonstrate the hardness of tissue. Blue and total areas of each section were measured to calculate the hardness of each LN. Results: Sixty‐nine LNs were evaluated by elastography. Twenty percent of LNs were malignant. There was a statistical difference between malignant and non‐malignant nodes based on color dominancy ( P  = 0.032). However, with the exclusion of anthracosis nodes from the analysis, the difference was more significant ( P  < 0.001). Moreover, when the blue dominancy was used as the predictor of malignancy or anthracosis, the results showed a significant correlation ( P  < 001). Conclusion: The usefulness of elastography in selecting the hardest area of tissue that is appropriate for diagnosing diseases has been proven previously. Since in countries with a high prevalence of anthracosis, blue color achieved using elastography predicts either malignancy or anthracosis so, cases with blue dominancy of LNs in elastography and the white color in the EBUS‐TBNA indicate anthracosis‐caused calcification should be reconsidered.